Emotional and Behavioural Symptoms, Risk Behaviours and Academic Success in Chilean Mapuche and Non-Mapuche Adolescents - Vera-Villarroel, P (Routledge, 2020)
Introduction: There is controversy over the real existence of differences in mental health and academic performance between the Mapuche ethnic minority male adolescents and the male adolescents not belonging to this ethnicity in Chile. Objective: In consequence, the aim of this study was to investigate the differences in emotional and behavioural symptoms, risky behaviours and academic success on the Chilean Mapuche and non-Mapuche adolescents. Design: The sample consisted of 233 adolescents of which 119 were Mapuche adolescents and 114 were non-Mapuche adolescents. Results: The results showed that the Mapuche adolescents do not have more anxiety problems and depression than the non-Mapuche adolescents. Furthermore, the Mapuche adolescents present less drug consumption and behavioural problems. Moreover, there were no differences in academic performance. Conclusions: This study provides social interest data of the adolescents mental health, which can be useful for the country s socio-sanitary and political decisions. Future studies should investigate these and other variables related to the mental health of minorities in greater depth. © 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group.